Search for sterile neutrinos mixing with muon neutrinos in MINOS - Adamson, P; Anghel, I; Aurisano, A; Barr, G; Bishai, M; Blake, A; Bock, G; Bogert, D; Cao, S; Carroll, T; Castromonte, C; Chen, R; et al. (American Physical Society, 2016)
We report results of a search for oscillations involving a light sterile neutrino over distances of 1.04 and 735 km in a ν_{μ}-dominated beam with a peak energy of 3 GeV. The data, from an exposure of 10.56×10^{20} protons on target, are analyzed using a phenomenological model with one sterile neutrino. We constrain the mixing parameters θ_{24} and Δm_{41}^{2} and set limits on parameters of the four-dimensional Pontecorvo-Maki-Nakagawa-Sakata matrix, |U_{μ4}|^{2} and |U_{τ4}|^{2}, under the assumption that mixing between ν_{e} and ν_{s} is negligible (|U_{e4}|^{2}=0). No evidence for ν_{μ}→ν_{s} transitions is found and we set a world-leading limit on θ_{24} for values of Δm_{41}^{2}≲1  eV^{2}.